Les agglomérations du Centre de la Gaule : types d’occupations et évolution du réseau (iiie-vie s. apr. J.-C.) - Christian Cribellier (Gallia)
The urban network of Central Gaul has expanded from Iron Age settlements. From the end of the 2nd-early 3rd c. AD, this network has changed while the civitas capitals were subjected to a retraction phenomenon and to major changes in town planning. Expansion or abandonment; the other towns had various destinies. New hill sites as well as small defensive settlements emerge, some of which are connected to existing towns. The mentions of vicus, castrum and castellum in Gregory of Tours writings give to these sites a historical anchor attested by some archaeological discoveries. It is thus a restructured and deeply changed network, inheriting from successive evolutions, which still lasted at the end of antiquity. As for the future of these towns in the early Middle Age, it is difficult to consider it. In concreto, their occupation patterns are being discussed. Interpreting them is not easy and a reassessment is required about survival of urban sites, foundation of new nucleated centres, small fortified sites, which lead or not to the birth of castra at the end of the period being studied or in the Carolingian period.